2016
DOI: 10.1002/nau.22993
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of autonomic nervous system function in children with overactive bladder syndrome

Abstract: This study demonstrated a parasympathetic hyperactivity in children with OAB, results suggesting a dysfunction in their autonomic nervous systems. Neurourol. Urodynam. 36:673-676, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For example, Fazeli et al, who evaluated 40 children with BBD and compared them to a control group of 19 children, reported less heart rate variability in patients with BBD (7). Likewise, Demir et al evaluated 40 children with OAB and 28 controls and showed greater heart rate variability during the Valsalva maneuver in participants of the control group (8). The sample size could have affected the ability of the study to detect a difference between some variables, increasing the likelihood of a type 2 error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fazeli et al, who evaluated 40 children with BBD and compared them to a control group of 19 children, reported less heart rate variability in patients with BBD (7). Likewise, Demir et al evaluated 40 children with OAB and 28 controls and showed greater heart rate variability during the Valsalva maneuver in participants of the control group (8). The sample size could have affected the ability of the study to detect a difference between some variables, increasing the likelihood of a type 2 error.…”
Section: Discussionmentioning
confidence: 99%
“…Demir et al analyzed 40 children with OAB and 28 controls. They revealed a better urinary dynamic function at the control group compared to the OAB group (8).…”
Section: Introductionmentioning
confidence: 92%
“…Patients with OAB may experience bladder dysfunction due to autonomic nervous system disorder. Multiple studies have evaluated ANS activity using neurophysiological diagnostic methods to test this hypothesis [20][21][22][23][24][25][26][27]:…”
Section: Digesu Et Al 2003 [16]mentioning
confidence: 99%
“…Ates et al demonstrated disrupted sympathetic function with OAB based on the skin sympathetic response test to assess sudomotor activity and function of thin unmyelinated sympathetic nerve fibers in the bladder and bladder neck [24,31].…”
Section: Digesu Et Al 2003 [16]mentioning
confidence: 99%
“…In patients with idiopathic bladder dysfunctions (IB), neurological examinations fail to reveal any pathology in the nervous system. Diagnosis of IB is not so obvious, as some studies demonstrated various pathologies in the nervous system, such as parasympathetic hyperactivity in children diagnosed with idiopathic OAB syndrome, suggesting a neurogenic dysfunction in their autonomic nervous system [ 13 15 ].…”
Section: Causes Of Neurogenic Lower Urinary Tract Dysfunctionsmentioning
confidence: 99%